Discovering ethnic minority business research directions using text mining and topic modelling - Moro, Sérgio (2022)
Purpose: This study aims to unveil within the current academic literature the principal directions in the ethnic entrepreneurship and small business marketing research context. Design/methodology/approach: An automated literature analysis procedure was undertaken, attempting to cover all literature published on the subject since 1962. A total of 188 articles were analysed using text mining and topic modelling. Findings: The results show a lack of framing of ethnic entrepreneurship literature outside the narrower scope of migration. Some core themes were found (e.g. network, diversity) around which several other themes orbit, including both related issues to the ethnic factor (e.g. barriers and minorities) and managerial issues (e.g. marketing and production). Originality/value: Ethnic minority business and small business marketing research has seen a growing number of publications. However, a careful review of existing work is missing.